Excitation of plasmon resonances on nanowire and nanoshell by complex source point - Stognii, N. P.; Sakhnenko, N. K. (IEEE, 2016)
Transient pulsed excitation of the localized surface plasmons on nanowire and nanoshell is visualized and analyzed. The complex source point concept is used to simulate an incident transient beam. Rigorous mathematical method based on the Laplace transformation is applied. Time domain field representation is obtained through the evaluation of the residues at singular points associated with the eigenvalues of the structure and integrals along the branch-cuts on the complex plane.
Keywords: Localised surface plasmons; plasmon resonances; complex source point